A RAPID AND SENSITIVE LIQUID CHROMATOGRAPHY- MASS SPECTROMETRY/MASS SPECTROMETRY METHOD FOR ESTIMATION OF PIOGLITAZONE, KETO PIOGLITAZONE AND HYDROXY PIOGLITAZONE IN HUMAN PLASMA - Ponnuri, Revathi Naga Lakshmi; Pragallapati, Prahlad; N, Ravindra; Mandava, Venkata Basaveswara Rao (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: The main objective of the work was to develop a straightforward, fast and selective liquid chromatography/tandem mass spectrometry (LC-MS/MS) assay for determination of pioglitazone (PG), keto pioglitazone (KPG), and hydroxy pioglitazone (HPG) in human plasma and to validate as per recent guidelines. Methods: Analyte and the internal standard (IS) were extracted from plasma through liquid-liquid extraction and chromatographed on a Xterra RP18, 100Ã—4.6, 5 Î¼ column using methanol: acetonitrile mixture and 10 mM Ammonium formate buffer (70:30, v/v) as the mobile phase at a flow rate of 0.7 mL/min. The API-3200 Q Trap LC-MS/MS instrument in multiple reaction monitoring mode was used for detection. Diphenhydramine was utilized as IS. Results: The linearity was established in the concentration range of 20.15-1007.58 ng/mL for PG, 20.35-1017.58 ng/mL for KPG, and 19.68-491.22 ng/mL for HPG in human plasma. All the validation parameters were well within the acceptance limits. Conclusion: A new simple LC-MS/MS method was developed for the determination of PG, KPG, and HPG in human plasma. This method can be easily applied for the estimation of pharmacokinetic parameters of PG, KPG, and HPG.